Effect of the use of ultrasound in the ultrafiltration process of cajá-manga pulp (Research, Society and Development, 2021)
The membrane filtration process is a promising alternative for the purification of extracts rich in bioactive compounds, but some drawbacks should be considered such as the membrane fouling. Thus, the aim of the present study was the evaluation of membrane filtration assisted by ultrasound in the purification of cajá-manga extract. Pretreatment with microfiltration membrane (0.8 µm) was efficient in clarifying the extract, with a reduction of 92% and 22% for turbidity and total solids, respectively. The application of ultrasound increased the flow by 64% for the 50 kDa membrane and only 16% for the 150 kDa membrane. In addition, there was a significant improvement in the stabilized flow for ultrasound filtrations, with stabilized flows increasing by 35% for the 50 kDa membrane and 32% for the 150 kDa membrane. The total solids content after the ultrasound-assisted membrane filtration process decreased by 20% and 7%, for the 50 kDa and 150 kDa membranes, respectively. The scanning electron microscopy indicated that there was a greater agglomeration of particles in the membranes in the process without ultrasound after the permeation of the extract. The results suggest that the sequential pre-treatment process (microfiltration) and filtration through ultrasound assisted ultrafiltration membranes can potentially be applied to produce clarified cajá-manga extracts, with significant levels of bioactive compounds and low fouling in the filtration process.